Life Cycle Cost Analysis of Maintenance Approaches for High-Wear Components in PVC Pipe Extruders: A Systematic Review - Oyewo, Abideen Temitayo; Olajire, Samson Oludare; Onawumi, Samuel Sunday (Borobudur Engineering Review, 2025)
Screws, barrels, and dies are high-wear parts in PVC pipe extruders; therefore, implementing an efficient maintenance plan to guarantee maximum productivity and reduce overall cost of production in plastics manufacturing. This paper used a systematic review of academic literature (2018”“2025) and performed an LCC analysis to evaluate corrective, preventive, and predictive maintenance approaches. The assessable cost factors consisted of labour cost, production downtime, replacement of spare parts, and effect of maintenance on the resource of the component. Further, it was discovered that the corrective maintenance which took a reactive approach had a low first cost but high cost throughout the use of equipment due to repetitive breakdowns and unscheduled downtimes. The application of preventive maintenance, as a way to minimize the risk of dangerous failures, led to moderate costs as a result of possible over-maintenance. CBM self-organized to condition-based monitoring and use of big data allowed for the development of a predictive maintenance strategy, which proved more cost-effective than the other three. The advantages of PM include decreased down time, increased component durability, increased reliability, and overall reduced costs for the system’s life cycle. These findings call for the implementation of preventive measures on the PVC pipe extruder systems to optimize manufacturing and cut costs in the long run for increased reliability of manufacturing processes